Africa's new electoral playbook - Ronak Gopaldas (2020)
With almost 20 elections scheduled in Africa this year, a rethink of the pre-conceived ideas around elections on the continent is definitely in order. Examination of the actions and reactions of incumbents and opposition politicians around these periods reveals the emergence of a new electoral playbook. The key focii of this paper are to deconstruct this playbook, containing the methods that stakeholders may employ to achieve their objectives, to identify the associated governance implications. The paper will use specific examples from across the continent to identify and assess emerging and evolving trends, and provide a framework to reveal (as Nic Cheeseman and Jeffry Smith argue in their January 2019 article for Foreign Affairs) whether and why “democracy is in retreat”. Finally, the paper will conclude by assessing future implications and outlooks for actions to halt the threats to electoral accountability and governance on the continent.